👤
a fost răspuns

efectueaza prin factor comun:
(a+12)la a doua +(a+12)
2(y-7)+(y-7)la a doua
(a+b)la a treia -(a+b)la a doua
x(x+7)-3(x+7)la a doua

(nu este totul la a doua/a treia,este doar operatia din fata textului)


Răspuns :

[tex] {(a + 12)}^{2} +( a + 12) = (a +1 2)(a + 12 + 1) = (a + 12)(a + 13)[/tex]

[tex]2(y - 7) + {(y - 7)}^{2} =( y - 7)(2 + y - 7) = (y - 7)(y - 5)[/tex]

[tex] {(a + b)}^{3} - {(a + b)}^{2} = {(a + b)}^{2}(a + b - 1)[/tex]

[tex]x(x + 7) - 3 {(x + 7)}^{2} = (x + 7)(x - 3(x + 7)) = (x + 7)( - 2x - 21) [/tex]